“If you don’t act, you are not going to get anything”: Professional identity and gender equality in Greek and Cypriot media organisations - Gazi, Angeliki; Dimitrakopoulou, Dimitra (MedieKultur: Journal of media and communication research, 2016)
The research here focuses on the relationship between women and media organisations in Greece and Cyprus. Our aim is to study the professional identity of women in the context of media organisations as well as the progress toward gender equality in Greek and Cypriot media organisations compared to the rest of Europe. Greece and, to a greater extent, Cyprus are societies in which the preservation and reproduction of the structure of the family constitutes the primary mechanism for socialization and professional accomplishment, much more than in other countries of central and northern Europe. The reported results are part of a more broadly focused EIGE Report entitled “Advancing gender equality in decision-making in media organizations,” which reviews the implementation of the Beijing Platform for Action (BPfA) in Member States. The BPfA, in turn, introduces the first indicators for measuring the progress of gender equality for women in the media. The media sectors both in Greece and Cyprus continue to be male-dominated. Women occupy only a small percentage of decision-making posts in media organisations. Moreover, there is a significant lack of gender-related policies and monitoring mechanisms in the media organisations and the countries themselves.